THE STUDY OF INDICATRICES OF SPACE OBJECT COATINGS IN A CONTROLLED LABORATORY ENVIRONMENT - Koshkin, N.; Burlak, N.; Petrov, M.; Strakhova, S. (Одеські астрономічні публікації, 2016)
The indicatrices of light scattering by radiation balance coatings used on space objects (SO) were determined in the laboratory experiment in a controlled condition. The laboratory device for the physical simulation of photometric observations of space objects in orbit, which was used in this case to study optical properties of coating samples, is described. The features of light reflection off plane coating samples, including multi-layer insulation (MLI) blankets, metal surfaces coated with several layers of enamel EP-140, special polyacrylate enamel AK-512 and matte finish TpCO-2, were determined. The indicated coatings are compound reflectors which exhibit both diffuse and specular reflections. The data obtained are to be used in the development of computer optical-geometric models of space objects or their fragments (space debris) to interpret the photometry results for real space objects.